(untitled) (Research, Society and Development, 2021)
Poultry farming has spread widely across the country. Despite their rustic characteristics, these birds are susceptible to serious diseases such as salmonellosis and avian coccidiosis. The objective was to investigate the infectious agents of these diseases in free-range chickens destined for school feeding in the city of São Luís, MA. A clinical examination of 198 birds was carried out, which consisted of observing the appearance of the plumage, beak, ridges, cloaca region and body condition. The samples were analyzed for Salmonella spp. following the methodology of the Ministry of Agriculture, Livestock and Supply . Of the 99 samples of cloaca (group of two birds), collected for investigation of Salmonella spp., 10 (10.1%) samples were suspected of the bacterium in biochemical tests, however all were negative (0%) due to antigenic serotyping. The survey and enumeration of Eimeria spp. The centrifugal flotation method was used in a sucrose solution. In the count of Eimeria spp. Oocysts, Of the 124 samples collected from the intestine during evisceration, 92 (74.19%) presented oocysts of the parasite, with counts ranging from 100 to 18,800 oocysts. The results were considered expected since, in a free-range chicken breeding system, where cocciostatic drugs are not used, the prevalence of Eimeria spp. it is often high. Therefore, it can be concluded that free-range chickens destined for slaughter in the municipality of São Luís did not present isolation for Salmonella spp., But did have a high incidence of infection by Eimeria spp.